After the Iran deal: Competing visions for Israel's nuclear posture. Issue 2 (14th March 2016) - Wolf, Albert B.
ABSTRACT: This article investigates the nuclear postures available to Israel in the wake of the Joint Comprehensive Plan of Action (JCPOA) between Iran and the P5 + 1. An "existential bias" pervades much of the literature on nuclear postures. Most scholars assume that once a state acquires the bomb it can deter all forms of aggression. However, recent scholarship has shown this to be untrue given that regional nuclear powers operate under much greater constraints than the U.S. and Russia or the Soviet Union. Israel faces tradeoffs between three postures: a catalytic posture, which would involve greater reliance upon the U.S.; assured retaliation, its current posture; and first use. Should Jerusalem continue to fear the prospect of abandonment by the U.S., it may turn to a first-use posture in order to leverage its conventional and nuclear superiority over its neighbors.